ANALISIS KOMPARATIF KUALITAS LABA SEBELUM DAN SESUDAH PENGUMUMAN KASUS COVID-19 DI INDONESIA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019 – 2020 - Hidayah, Sarif; Rapel; Leliana Maria Angela (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
This research aims to determine the difference in the earnings quality of company before and after the national announcement of Covid-19 cases in Indonesia in manufacturing companies. The Covid-19 pandemic has decreased the company's revenue so that it has the potential to cause company financial problems and information asymmetry. This can cause the management to potentially carry out earnings management so that it will affect the earnings quality. The variable used in this study is earnings quality. The indicator used to measure earnings quality is using Earnings Response Coefficients (ERC). This research was conducted on trading, service and investment sector companies listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling and there are 145 companies used in this research. The results of this research indicate that there is no significant difference between the earnings quality before and after the announcement of the Covid-19 pandemic in Indonesia.